A juvenile mouse model of anti-N-methyl-D-aspartate receptor encephalitis by active immunization - He, Shuyu; Sun, Chongyang; Zhu, Qian; Li, Lin; Huang, Jianyu; Wu, Ge; Cao, Yi; Liao, Jianxiang; Lu, Yi; Su, Qiru; Lin, Sufang; Ma, Xiaopeng; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a common autoimmune encephalitis, and it is associated with psychosis, dyskinesia, and seizures. Anti-NMDAR encephalitis (NMDARE) in juveniles and adults presents different clinical charactreistics. However, the pathogenesis of juvenile anti-NMDAR encephalitis remains unclear, partly because of a lack of suitable animal models. Methods We developed a model of juvenile anti-NMDAR encephalitis using active immunization with an amino terminal domain peptide from the GluN1 subunit (GluN1356 − 385) against NMDARs in 3-week-old female C57BL/6J mice. Results Immunofluorescence staining suggested that autoantibody levels in the hippocampus increased, and HEK-293T cells staining identified the target of the autoantibodies as GluN1, suggesting that GluN1-specific immunoglobulin G was successfully induced. Behavior assessment showed that the mice suffered significant cognition impairment and sociability reduction, which is similar to what is observed in patients affected by anti-NMDAR encephalitis. The mice also exhibited impaired long-term potentiation in hippocampal CA1. Pilocarpine-induced epilepsy was more severe and had a longer duration, while no spontaneous seizures were observed. Conclusion The juvenile mouse model for anti-NMDAR encephalitis is of great importance to investigate the pathological mechanism and therapeutic strategies for the disease, and could accelerate the study of autoimmune encephalitis.